Peace ontologies, narratives, and epistemes among indigenous communities of Nigeria and Bolivia - Damilola Adegoke; Gloriana Rodriguez Alvarez (Frontiers in Political Science)
This study examines Indigenous peace ontologies and epistemologies among Nigerian and Bolivian communities, specifically the Yoruba, Ukwu-Nzu, Ubang, and Aymara cultures, to explore peace conceptual transformations through colonial and historical experiences. Conceptual representations and knowledge production are shaped by power dynamics that mainly marginalize Indigenous epistemic experiences, often erasing or replacing traditional ways of knowing with dominant, typically colonial ideologies. Using a qualitative cross-cultural exploratory approach—including semi-structured interviews, focus groups, and observations—the study reveals peace conceptualizations rooted in cosmological, historical, communal, and ecological frameworks. The Yoruba perceive peace as equilibrium mediated by Òrìṣà and personal agency, while the Aymara understand peace through suma qamaña— “living well” in harmony with Pachamama. Both perspectives emphasize collective well-being, relational ethics, and historical resilience. The study also examines the influence of Islam on Yoruba peace semiotics by reconstructing pre-Islamic peace terms in Lukumi, a Yoruboid language of the Ukwu-Nzu people, and explores gendered linguistic variations in peace conceptualization through the Ubang culture, where men and women speak mutually unintelligible languages. By critiquing universalist assumptions, the study advocates for decolonial methodologies that integrate Indigenous epistemes into broader scholarly discourses, fostering inclusive and pluralistic understandings of peace.